Efficacy of Low-Intensity Cognitive Behavior Intervention for Chinese Delinquent Youth. (February 2022) - Zhuang, Xiaoyu; Lau, Yin Yim; Huang, Yu-Te; Tam, Cherry Hau Lin; Chan, Wilson Man Ho; Yeung, Kenneth Kin Wa; Ng, Ting Kin; Wong, Daniel Fu Keung
Purpose: Recent literature has pointed out the seriously unmet treatment needs of delinquent youth with mental health problems in Hong Kong. This study pioneers to systematically develop and evaluate the effectiveness of a structured low-intensity cognitive behavioral intervention (LICBI) to concurrently address mental health issues and delinquent behaviors among Hong Kong Chinese youth. Method: A quasi-experimental controlled design was adopted with three assessments at baseline, postintervention, and 6-week follow-up. One hundred and eighty participants were recruited to the LICBI and 123 to the control group. Results: Multilevel modeling analyses showed that the LICBI might be effective in improving mental health–related factors (impulsivity, self-esteem, negative emotions, and loneliness) and delinquent behaviors. A mediation analysis suggested that LICBI might reduce participants' delinquent behaviors through reducing their impulsivity and enhancing their self-esteem. Discussion: The results provide preliminary evidence for the effectiveness of LICBI for Chinese delinquent youth in a community social service setting.